1993
DOI: 10.1093/hmg/2.11.1921
|View full text |Cite
|
Sign up to set email alerts
|

Functional evidence for a breast cancer growth suppressor gene on chromosome 17

Abstract: Rearrangements or deletions of chromosome 17 are the most frequently observed genetic changes identified in breast tumors. Molecular analyses suggest that in addition to the p53 gene on 17p13.1 there may be at least three other tumor suppressor genes on chromosome 17 involved in breast cancer. Regions of loss of heterozygosity (LOH) identified on 17p13.3 and 17q12-qter occur frequently in breast tumors, and the BRCA-1 gene has been mapped to 17q21 by genetic linkage analysis. Here we provide biological evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…Analysis of the immortal phenotype has revealed several genetic alterations that are important to the process including the dysfunction of p53, INK4A and a gene on chromosome 3p that represses telomerase activity (Loughran et al, 1997;Parkinson et al, 1997). In addition, microcell-mediated monochromosome transfer (MMCT) experiments suggest that other cancer mortality genes may exist (Casey et al, 1993;Hensler et al, 1994;Karlsson et al, 1996;Koi et al, 1993;Ning et al, 1991;Ogata et al, 1993;Rimessi et al, 1994;Sandhu et al, 1994Sandhu et al, , 1996Sasaki et al, 1994;Uejima et al, 1995;Wang et al, 1992). Furthermore, loss of heterozygosity (LOH) at some of these other chromosomal loci, including the long arm of chromosome 4, supports a role for the dysfunction of these putative mortality genes in the immortality of human SCCs (Loughran et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the immortal phenotype has revealed several genetic alterations that are important to the process including the dysfunction of p53, INK4A and a gene on chromosome 3p that represses telomerase activity (Loughran et al, 1997;Parkinson et al, 1997). In addition, microcell-mediated monochromosome transfer (MMCT) experiments suggest that other cancer mortality genes may exist (Casey et al, 1993;Hensler et al, 1994;Karlsson et al, 1996;Koi et al, 1993;Ning et al, 1991;Ogata et al, 1993;Rimessi et al, 1994;Sandhu et al, 1994Sandhu et al, , 1996Sasaki et al, 1994;Uejima et al, 1995;Wang et al, 1992). Furthermore, loss of heterozygosity (LOH) at some of these other chromosomal loci, including the long arm of chromosome 4, supports a role for the dysfunction of these putative mortality genes in the immortality of human SCCs (Loughran et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, LOH at YNZ22 can occur in the absence of p53 mutation, deletion or over-expression (Cornelis et al, 1994;Thompson et al, 1998) suggesting both regions may be of clinical importance in sporadic breast cancer Liscia et al, 1999). In addition, supportive evidence for the involvement of a tumour suppressor gene, distinct from p53 on chromosome 17p, is strengthened by the functional suppression of malignancy observed following the transfection of chromosome 17 (but not with chromosome 13) into breast cancer cell lines by micro cellmediated chromosome transfer and analysis of the resulting deletions (Casey et al, 1993;Theile et al, 1995). LOH at 17p13.3 is also associated with an aggressive phenotype being significantly correlated with disease recurrence and death due to breast cancer Nagai et al, 1995).…”
mentioning
confidence: 96%
“…Genetic analysis of the immortal phenotype has revealed several genetic alterations that are important to the process including the dysfunction of p53, INK4A and a gene on chromosome 3p that represses telomerase activity (Loughran et al, 1997;Parkinson et al, 1997). In addition, microcell-mediated monochromosome transfer (MMCT) experiments suggest that other cancer mortality genes may exist (Ning et al, 1991;Wang et al, 1992;Casey et al, 1993;Koi et al, 1993;Ogata et al, 1993;Hensler et al, 1994;Rimessi et al, 1994;Sandhu et al, 1994Sandhu et al, , 1996Sasaki et al, 1994;Uejima et al, 1995;England et al, 1996;Karlsson et al, 1996;Robertson et al, 1998;Cuthbert et al, 1999;Steenbergen et al, 2001;Forsyth et al, 2002). Loss of heterozygosity (LOH) at some of these chromosomal loci supports a role for the dysfunction of these putative mortality genes in the immortality of human SCCs (Loughran et al, 1997;Forsyth et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have used the technique of monochromosome transfer to induce proliferation arrest in human and rodent cancer lines (Ning et al, 1991;Wang et al, 1992;Casey et al, 1993;Koi et al, 1993;Ogata et al, 1993;Hensler et al, 1994;Rimessi et al, 1994;Sandhu et al, 1994Sandhu et al, , 1996Sasaki et al, 1994;Uejima et al, 1995;England et al, 1996;Karlsson et al, 1996;Banga et al, 1997;Robertson et al, 1998;Cuthbert et al, 1999;Steenbergen et al, 2001) and have attempted to identify the genes responsible by the extensive deletion analysis of segregant colonies that continue to proliferate (see for example, Rimessi et al, 1994;England et al, 1996;Karlsson et al, 1996;Robertson et al, 1998;Cuthbert et al, 1999;Forsyth et al, 2002). These studies have shown that, in some instances, the commonly deleted regions contain known antiproliferative genes (England et al, 1996;Robertson et al, 1998) or tumour suppressor genes (Cheng et al, 1998;Lo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%